Scale-up of the electrokinetic fence technology for the removal of pesticides. Part I: Some notes about the transport of inorganic species. (January 2017) - López-Vizcaíno, R.; Risco, C.; Isidro, J.; Rodrigo, S.; Saez, C.; Cañizares, P.; Navarro, V.; Rodrigo, M.A.
Abstract: This work describes the application electrokinetic fence technology to a soil polluted with herbicides in a large prototype containing 32 m 3 of soil. It compares performance in this large facility with results previously obtained in a pilot-scale mockup (175 L) and with results obtained in a lab-scale soil column (1 L), all of them operated under the same driving force: an electric field of 1.0 V cm −1 . Within this wide context, this work focuses on the effect on inorganic species contained in soil and describes the main processes occurring in the prototype facility, as well as the differences observed respect to the lower scale plants. Thus, despite the same processes can be described in the three plants, important differences are observed in the evolution of the current intensity, moisture and conductivity. They can be related to the less important electroosmotic fluxes in the larger facilities and to the very different distances between electrodes, which lead to very different distribution of species and even to a very different evolution of the resulting current intensity. 2-D maps of the main species at different relevant moments of the test are discussed and important information is drawn from them. Ions depletion from soil appears as a very important problem which should be prevented if the effect of natural bioremediation and/or phytoremediation on the removal or organics aims to be accounted. Graphical abstract: Highlights: In EK soil remediation technology, size of the experimental setup matters. Same processes occurring, different observations made because of the dimensions. Increase in the intensity over the experiment due to the conductivity and pH. Depletion of ions from soil and concentration in the nearness of electrode wells. Rapid dynamic response: almost no relevant changes after a 15-day treatment.